Variation in Translation and Peculiarities of its Understanding in the Light of the Theory of Intercultural Communication - Tomash Vrabel; Vrábely Tamás; Врабель Томаш (Cognum Publishing House, 2020)
Abstract. This paper deals with variation in translation caused by the translator’s understanding of a text created in a different cultural environment. The notion of understanding is given as defined by leading researchers in the field. The concept of variation in translation is analysed side by side with its causes and ways of eliminating it. The personality factor and its influence on the translation is studied. The author comes to the conclusion that the translator’s personality, his linguistic preferences of particular words, constructions, ways of translation, etc. exert great influence on translation in general and eliminating variation in translation in particular.
Keywords: variation in translation; intercultural communication; understanding translation; equivalence; identity; source text; target text